Training on the Utilization of Lime to Empower the Lime Farmers in Bolo Village, Gresik - Idha Kusumawati; Sari Retno; Handayani Rosita; Harjono Suko; Yuwono Mochamad; Munandar Tristiana Erawati (UNUSA Press, 2023)
Lime (Citrus aurantifolia (Christm.) Swingle) is one of the important agricultural commodities for residents in the Bolo village, Gresik. The resident of Bolo Village owns an average of 1/4 hectare of lime plantations. However, the price of lime is not stable. In the harvest season, when conditions become surplus in the market, lime prices often drop, causing losses for the farmers. Lack of knowledge about lime product processing is also an obstacle in the utilization and processing of crops. This community service activity aims to improve the knowledge and skills of citrus farmers in Bolo Village to utilize and process lime crops into Home Industry products, so they do not suffer losses when the lime price drops. Activities are carried out through learning using interactive lecture methods and training through product manufacturing demos. The successful indicator was carried out by evaluating the participants' level of understanding before and after the activity. The training activities significantly increased the participants' knowledge and experience. In addition, this activity also obtained data on the needs of lime farmers. It is hoped that this data can be used for the continuation of the next activity or can also be used by the local government, which wants to help advance agriculture and product diversification in the village of Bolo.